Reproducibility of human cardiac phosphorus MRS (31P‐MRS) at 7 T. (29th March 2019) - Ellis, Jane; Valkovič, Ladislav; Purvis, Lucian A.B.; Clarke, William T.; Rodgers, Christopher T.
Abstract : Purpose: We test the reproducibility of human cardiac phosphorus MRS ( 31 P‐MRS) at ultra‐high field strength (7 T) for the first time. The primary motivation of this work was to assess the reproducibility of a 'rapid' 6½ min 31 P three‐dimensional chemical shift imaging (3D‐CSI) sequence, which if sufficiently reproducible would allow the study of stress‐response processes. We compare this with an established 28 min protocol, designed to record high‐quality spectra in a clinically feasible scan time. Finally, we use this opportunity to compare the effect of per‐subject B 0 shimming on data quality and reproducibility in the 6½ min protocol. Methods: 10 healthy subjects were scanned on two occasions: one to test the 28 min 3D‐CSI protocol, and one to test the 6½ min protocol. Spectra were fitted using the OXSA MATLAB toolbox. The phosphocreatine to adenosine triphosphate concentration ratio (PCr/ATP) from each scan was analysed for intra‐ and intersubject variability. The impact of different strategies for voxel selection was assessed. Results: There were no significant differences between repeated measurements in the same subject. For the 28 min protocol, PCr/ATP in the midseptal voxel across all scans was 1.91 ± 0.36 (mean ± intersubject SD). For the 6½ min protocol, PCr/ATP in the midseptal voxel was 1.76 ± 0.40. The coefficients of reproducibility (CRs) were 0.49 (28 min) and 0.67 (6½ min). Per‐subject B 0 shimming improved the fitted PCr/ATP precision (for 6½ min scans), but had negligible effect on the CR (0.67 versus 0.66). Conclusions: Both 7 T protocols show improved reproducibility compared with a previous 3 T study by Tyler et al. Our results will enable informed power calculations and protocol selection for future clinical research studies. Abstract : We test the reproducibility of two 3D 31P‐MRS CSI protocols at 7 T: one lasting 28 minutes and one lasting 6½ minutes. We observed improved reproducibility even in 6 ½ minutes at 7 T compared to previously reported results for a 31 minute scan at 3 T. Our findings can be used for power calculations when designing future clinical studies using 7 T 31 P‐MRS as an endpoint.